ALIGNMENT OF LEARNING ACTIVITIES AND ASSESSMENT TASKS IN ENGLISH TEXTBOOK “WHEN ENGLISH RINGS A BELL” - Umbari, Tiara; Soendarti, Mamiek; Supeno, Supeno (INFERENCE: Journal of English Language Teaching, 2023)
The aim of the research is to analyze the alignment of Learning Activities and Assessment Tasks in the English text book “When English Rings a Bell. This study was descriptive qualitative approach. The instrument used to collect the data is document study used in the form of checklist. Three checklists were made adopted from previous studies. The results of this study showed that the alignment of Learning Activities in the textbook achieved score 82% based on the Basic Competence Standards statements 3 and 4. Meanwhile Assessment Tasks in text book are aligned with 78% Basic Competence Standards statements 3 and 4. Then, the English textbook “When English Rings a Bell” is categorized ‘partially aligned’ with 2013. It can be concluded that textbook is suitable to be used in order to help the teaching learning process in the classroom with the help of other sources and teacher adaptation.Key Words: text book; alignment; 2013 Curriculum